Pengembangan Grafik Rancang Awal Fondasi Tiang untuk Struktur Overland Conveyor: Pendekatan Praktis Berbasis Data Geoteknik - Laksita, Aisya Galuh; Darmawan, Angga (Universitas Muhammadiyah Palembang, 2025)
Overland Conveyors (OLC) are widely recognized as a reliable and energy-efficient solution for bulk material transport in modern mining operations. However, their structural integrity is highly dependent on a foundation system capable of safely resisting axial, tensile, and lateral loads—especially when constructed across diverse and challenging subsoil conditions. This study presents a geotechnical-based analytical approach to estimate the single-pile capacity of bored and driven piles along the proposed OLC alignment in East Kalimantan, Indonesia. Subsurface investigations from 23 boreholes, comprising SPT and CPT data, were used to evaluate bearing capacity for pile diameters ranging from 0.3 to 1.0 meters and depths up to 50 meters. Load demands were assumed based on preliminary structural considerations: 2000 kN axial load and 280 kN lateral load per foundation unit. The analysis incorporates empirical methods for axial and uplift capacity, adjusted for dominant soil types, while lateral capacity was assessed using Broms’ method. Results are visualized through a set of design-friendly graphs, enabling rapid configuration assessment (single or grouped piles) without the need for finalized structural loads. These graphs serve as a practical tool for early-stage design exploration, helping engineers balance safety, constructability, and cost. Ultimately, this research offers not only a systematic method for selecting efficient pile configurations under variable geotechnical profiles, but also reinforces the importance of field data-driven foundation planning for resilient and cost-effective OLC infrastructure.